Genome-wide construction of a series of designed segmental aneuploids in Saccharomyces cerevisiae - Natesuntorn, Waranya (Sci Rep, 2015)
Segmental aneuploidy can play an important role in environmental adaptation. However, study of segmental aneuploids is severely hampered by the difficulty of creating them in a designed fashion. Here, we describe a PCR-mediated chromosome duplication (PCDup) technology that enables the generation of segmental aneuploidy at any desired chromosomal region in Saccharomyces cerevisiae. We constructed multiple strains harboring 100 kb to 200 kb segmental duplications covering the whole of the S. cerevisiae genome. Interestingly, some segmental aneuploidies confer stress tolerance, such as to high temperature, ethanol and strong acids, while others induce cell lethality and stress sensitivity, presumably as result of the simultaneous increases in dosages of multiple genes. We suggest that our PCDup technology will accelerate studies into the phenotypic changes resulting from alteration of gene dosage balance of multiple genes and will provide new insights into the adaptive molecular mechanisms in the genome in segmental aneuploidy-derived human diseases.